New worlds of logistical labour: Spaces, places, technologies, workers - Tom Barnes; Christopher O’Neill; Lauren Kelly (Work Organisation, Labour and Globalisation, 2025)
This Special Issue offers new research on the dynamic interaction and interdependence of global logistics with spaces of labour, including work, workers, organisations and workers’ communities. It presents ten articles that emphasise the changing nature of logistical labour in the context of radical technological transformation and changing spatial and social configurations. Spanning diverse geographical contexts across five continents, the collection offers three key interventions. First, it demonstrates that contemporary logistics is blurring the analytical boundaries that traditionally divide places of work and industry. Second, it provides new insights into the multifarious and reciprocal relations between technology and labour. Third, it brings fresh perspectives to debates about continuity versus novelty in contemporary work, addressing issues such as labour displacement, labour augmentation, workplace regimes and algorithmic management. While reiterating the widespread and ongoing influence of despotic workplace practices in logistics globally, the collection challenges assumptions of geographical universalism that characterise much modern debate about logistical labour.